2017
DOI: 10.1186/s13011-017-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality measurers of therapeutic communities for substance dependence: an international collaborative study survey in Latin America

Abstract: BackgroundIn Latin America, substance related disorders are highly prevalent and one of the treatment strategies is the Therapeutic Communities (TCs), however, in Latin America there is scarce data about this treatment strategies, their quality, drop-out rates and patient satisfaction.MethodsBased on a previous study in 5 Latin American countries, the TCs who had a score equal or higher than 9 according to the De Leon criteria which are some fundamental items that the TCs should meet, were selected to carry ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…Research has suggested that individuals who availed of the services of therapeutic communities showed a significant outcome of quitting substance use and they have improved psychosocial functioning (Vanderplasschen et al, 2013). Another evidence-based research has suggested that the patients (79%) who stayed in therapeutic communities have reported positive improvement in them revealing that these services are working (Gómez-Restrepo et al, 2017). However, the stay of patients at the rehabilitation center was based on medicinal treatment only.…”
Section: Theme 1: Experiences Of Individuals At the Rehabilitation Ce...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that individuals who availed of the services of therapeutic communities showed a significant outcome of quitting substance use and they have improved psychosocial functioning (Vanderplasschen et al, 2013). Another evidence-based research has suggested that the patients (79%) who stayed in therapeutic communities have reported positive improvement in them revealing that these services are working (Gómez-Restrepo et al, 2017). However, the stay of patients at the rehabilitation center was based on medicinal treatment only.…”
Section: Theme 1: Experiences Of Individuals At the Rehabilitation Ce...mentioning
confidence: 99%
“…Unlike this study, world experience shows that the role of the social worker in recovery is crucial (Daley and Feit, 2013) as one needs to make sure that the recovering person does not hook up again with the same peers who led him to addiction and that she or he receives family support; even families need support because a breadwinner’s addiction might leave a family economically, emotionally, and socially devastated (Kourgiantakis et al, 2021; Lander et al, 2013); community outreach plays an important role as studies show us (Gómez-Restrepo et al, 2017; Vanderplasschen et al, 2013).…”
Section: Theme 2: Recoverymentioning
confidence: 99%
“…(8) Dentro de las sustancias de mayor consumo engloba el alcohol, cafeína, cannabis, alucinógenos, inhalantes, opioides, hipnóticos, sedantes, tabacos y estimulantes. (9) Además, representa un conflicto de interés a nivel económico, político, social e igualmente dentro de los factores más predisponentes para que se desencadene esta problemática son los efectos psicosociales, los mismo que engloban, desde enfermedades con alteraciones a nivel molecular y celular, accidentes o situaciones relacionadas a su entorno familiar. (10,11) El estudio tiene la finalidad de recopilar información acerca de la calidad de vida de adictos a sustancias psicoactivas y las dificultades de adaptación a su entorno dado que no se han realizado previamente indagaciones, es de mayor énfasis en adultos ya que representan un grupo vulnerable para el consumo de sustancias ilícitas por diversos que pueden presentarse a corto o largo plazo.…”
Section: Introductionunclassified